Biogenic silver nanoparticles synthesized via Mimusops elengi fruit extract, a study on antibiofilm, antibacterial, and anticancer activities - Korkmaz, Nesrin; Ceylan, Yusuf; Hamid, Attia; Karadag, Ahmet; Bulbul, Ali Savas; Aftab, Muhammad Nauman; Cevik, Ozge; Ceylan, Yusuf (Elsevier, 2020)
Herein, a simple approach was used for synthesis of silver nanoparticles by Mimusops elengi liquid fruit extract. Mimusops elengi is an ornamental plant, well-known for its fragrant flowers. The fruit source acts as a reducing mediator. The reduction of silver ions of this work was explored by fruit extract in the solution. The characterization of prepared biogenic silver nanoparticles (AgNPs) was achieved by UV-vis spectroscopy, XRD analyses, and STEM. As a result of characterization, it showed a maximal absorbance in the UV-vis spectrum at a wavelength of similar to 431 nm. In the XRD analysis, five basic peaks attributed to Ag nanoparticles were observed. When STEM images were analysed, it was determined that Ag nanoparticles generally have a spherical shape and an average size of 43 nm AgNPs were tested antimicrobial activity with Enterococcus durans, Listeria innocua, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Salmonella enteritidis, Salmonella kentucky, Staphylococcus epidermidis Staphylococus aureus, Xanthomonas, and Proteus vulgaris. AgNPs demonstrated antibacterial activities against all tested Gram (+) and Gram (-) bacteria strains. AgNPs at a low concentration of 625 mu g/mL exhibited bacteriocidal effects on some tested bacteria. Further, antibiofilm tests were also performed. In addition, AgNPs inhibited 86.36% of the biofilm layer formed by the Escherichia coli bacteria at a concentration of 1250 mu g/mL. Last, but not least, anticancer activities were tested using human colon (HT-29) and breast (MCF7) cancer cell lines. AgNPs are one of the most effective IC50 values against HT-29 and MCF7 cancer cell lines, respectively, 155 mu g/mL at 24 h and 179 mu g/mL at 40 h. The rapid, eco-friendly and non-toxic synthesis of AgNPs obtained by green synthesis rises their potential to become an agent for biological activities such as antibacterial, antibiofilm, and anticancer.
Keywords: Anticancer; Bio-Reduction; Biofilm; Green Synthesis; Mimusops Elengi; Silver Nanoparticles